Escola e família: a importante parceria no desenvolvimento e aprendizagem das crianças - LOPES, Ana Luiza de Oliveira (2023)
The present work has as a theme school and family: the important partnership in the development and learning of children, in which we emphasize on Education, trying to show the relationship between school and family, and the important relation for the success of the child's learning. It is a qualitative research in the bibliographic and field modalities. The data collection techniques used were the observation and the semistructured interview conducted with the director, five teachers and ten parents / guardians of the students from the 1st to the 4th year of the initial series of elementary education at a municipal school located in the city of Castanhal, Pará. Through the interview with the director, teachers, parents, or caregivers, we realize the importance of having a harmonious relationship between the school and the family, so that children can have a greater advancement in development and success in school income. We sought to know in which term occurs the relationship between school and family in the initial series of elementary school of a public school in Castanhal. In response to the problem, what factors contribute to the separation between family and school, what unites or separates? And what can be done so that the school can bring the family closer to each other and together, while playing specific roles can help in the search for a better school performance of the children. With the research we realized that this relationship is of extreme importance for the child's life, having great relevance in the teaching process of the students, thus enabling a good school performance.